(untitled) (De Legibus - Law Journal, 2022)
Entering the maze of State succession, the present article aims to analyse and reflect on the problems raised by State succession at nationality level, giving special relevance to the (un)avoidable problem of statelessness. After a brief initial study of the general regime of State succession, there follows an analysis of the attribution and loss of nationality as a human right, with special emphasis on the complex issue of statelessness. By means of a cross-cutting approach to these two themes, this article then focuses on the study of the consequences of State succession in terms of nationality, based on the dynamic analysis of the European Court of Human Rights’s case of Kurić and Others v. Slovenia, which presents sui generis contours. The carried-out study leads to the formulation of some proposals to strengthen the fight against statelessness and to fill the various gaps in the Law of State Succession regarding nationality.